MiRNA profiling of biliary intraepithelial neoplasia reveals stepwise tumorigenesis in distal cholangiocarcinoma via the miR‐451a/ATF2 axis. Issue 3 (15th September 2020) - Loeffler, Moritz A; Hu, Jun; Kirchner, Martina; Wei, Xiyang; Xiao, Yi; Albrecht, Thomas; De La Torre, Carolina; Sticht, Carsten; Banales, Jesus M; Vogel, Monika N; Pathil‐Warth, Anita; Mehrabi, Arianeb; et al.
Abstract: Distal cholangiocarcinoma (dCCA) is a biliary tract cancer with a dismal prognosis and is often preceded by biliary intraepithelial neoplasia (BilIN), representing the most common biliary non‐invasive precursor lesion. BilIN are histologically well defined but have not so far been characterised systematically at the molecular level. The aim of this study was to determine miRNA‐regulated genes in cholangiocarcinogenesis via BilIN. We used a clinicopathologically well‐characterised cohort of 12 dCCA patients. Matched samples of non‐neoplastic biliary epithelia, BilIN and invasive tumour epithelia of each patient were isolated from formalin‐fixed paraffin‐embedded tissue sections by laser microdissection. The resulting 36 samples were subjected to total RNA extraction and the expression of 798 miRNAs was assessed using the Nanostring® technology. Candidate miRNAs were validated by RT‐qPCR and functionally investigated following lentiviral overexpression in dCCA‐derived cell lines. Potential direct miRNA target genes were identified by microarray and prediction algorithms and were confirmed by luciferase assay. We identified 49 deregulated miRNAs comparing non‐neoplastic and tumour tissue. Clustering of these miRNAs corresponded to the three stages of cholangiocarcinogenesis, supporting the concept of BilIN as a tumour precursor. Two downregulated miRNAs, i.e. miR‐451a (−10.9‐fold down) and miR‐144‐3p (−6.3‐fold down), stood out by relative decrease. Functional analyses of these candidates revealed a migration inhibitory effect in dCCA cell lines. Activating transcription factor 2 (ATF2) and A disintegrin and metalloproteinase domain‐containing protein 10 (ADAM10) were identified as direct miR‐451a target genes. Specific ATF2 inhibition by pooled siRNAs reproduced the inhibitory impact of miR‐451a on cancer cell migration. Thus, our data support the concept of BilIN as a direct precursor of invasive dCCA at the molecular level. In addition, we identified miR‐451a and miR‐144‐3p as putative tumour suppressors attenuating cell migration by inhibiting ATF2 in the process of dCCA tumorigenesis. © The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.